The sorption of Hydrochloric Acid and Potassium Hydroxide by mohair and wool - Bamford, Graeme Reginald Ernest (Rhodes University, Faculty of Science, Department of Chemistry, 1959)
The main object of the present investigation has been to establish a titration curve for mohair keratin and to compare it with similar data for wool, to determine whether the differences in physical and chemical properties could be attributed in any way to the acidic and basic character of these fibres. As shown in subsequent discussion such measurements provide extremely useful information regarding the chemical structure of proteins in general, and in the technical fields involving processes such as wool scouring, carbonizing and dyeing. The study has been extended to include certain modified wools, i.e. photochemically damaged, and oxidized keratin. The most successful contribution to the titration data of wool keratin is the work of Steinhardt and Harris and subsequent authors have tended to adopt their procedures without modification. In the present study attempts have been made to obtain a clearer understanding of the fundamental processes. New techniques and analytical methods have been introduced to improve the accuracy of the measurements.
Keywords: Hydrochloric acid -- Absorption and adsorption; Hydroxides -- Absorption and adsorption; Wool; Mohair